The effects of Wi-Fi radiation (2.45 ghz) on spermatogenesis and male reproductive system - Lev E. Belyi (LLC "MEDIAFORMAT", 2024)
Wireless communication (Wi-Fi) has become the preferred way of Internet communication and connectivity, has become a daily necessity and is widely used in a wide variety of devices. Widespread use of Wi-Fi (2.45 GHz) has significantly changed human life for the better, but has led to the widespread spread of radio frequency electromagnetic radiation. Scientific evidence suggests the possible negative effects of Wi-Fi on male fertility. This review examines the main pathogenetic mechanisms of male infertility due to the influence of wireless devices: oxidative stress, DNA fragmentation and apoptosis of male gametes. The results of in vitro experimental studies proving the effect of radiofrequency electromagnetic radiation on ejaculate are presented. The results of studies using in vivo experimental models were analyzed. This allowed us to get a holistic view of the effects of Wi-Fi on the male reproductive system and spermatogenesis. The presented new scientific data on the impact of everyday Wi-Fi use on spermatogenesis in men.